Social value, normative features and gender differences associated with speeding and compliance with speed limits. (February 2023) - Varet, Florent; Apostolidis, Thémis; Granié, Marie-Axelle
Highlights: Speeding is an important cause of crashes and is more frequent among males than females. We investigated gender social norms of judgment about speeding in two studies. Speeding is valued more on the social utility dimension than the desirability-one. Males less valuate speed limit compliance than females on social desirability. The representation of the compliant driver should be improved, especially among males. Abstract: Introduction : Among risky driving behaviors, speeding is a main causal and aggravating factor of road crashes and is more frequent among males than females. Research suggests that this gender gap could be explained by gender social norms that lead males to assign more social value to speeding than females. However, few studies have proposed directly investigating gendered prescriptive norms associated with speeding. We propose to address this gap through two studies based on the socio-cognitive approach to social norms of judgment. Methods: Study 1 ( N = 128, within-subject design) investigated the extent to which speeding is subject to social valuation among males, compared to females, through a self-presentation task. Study 2 ( N = 885, between-subject design) aimed to identify the dimension of social value (i.e., social desirability, social utility) that both genders associate with speeding, based on a judgment task. Results and conclusion : Although results of study 1 indicate that both genders devaluate speeding and valuate speed limits compliance, we found that males do so to a lesser extent than females. Results of study 2 further suggest that males less valuate speed limit compliance than females on the social desirability dimension, while no gender difference were found in valuation of speeding on both dimensions of social value. Regardless of gender, results also indicate that speeding is valued more on the social utility than on the social desirability dimension, while speed limit compliance is valued similarly on both dimensions. Practical applications : Road safety campaigns toward males could benefit to focus more on enhancing the representations of speed compliant drivers, in terms of social desirability, than devaluing the representation of speeding drivers.